Effectivity of water soluble granule from kenikir leaves extract (Cosmos caudatus), noni leaves extract (Morinda citrifolia), and earthworm meal extract (Lumbricus rubellus) as a natural coccidiostat for broiler chickens against infection caused by Eimeri - Karimy MF; Julendr H; Hayati SN; Sofyan a; Damayanti E; Priyowidodo D (Jurnal Ilmu Ternak dan Veteriner, 2013)
The aim of this research was to study effectivity of water soluble granule from kenikir leaves extract (Cosmos caudatus), noni leaves extract (Morinda citrifolia), and earthworm meal extract (Lumbricus rubellus) as a natural coccidiostat for broiler chickens against infection caused by Eimeria tenella. One hundred day old chick (DOC) of the Cobb strain broiler were randomly devided into 10 groups and each group consisted of 10 chickens. All groups were orally infected by 5000 sporulated oocyst of E. tenella on the 25th days old as a challenge infection. The chickens was treated by granule of kenikir leaves extract, noni leaves extract and granule of earthworm meal extract which level dosage was 100, 200 and 300 mg/kgbw, respectively on each treatment (K1, K2, K3; M1, M2, M3 and T1, T2, T3). Control (K0) did not treated by feed additive. Treatment was administered on drinking water. On the 5th days after challenge infection 5 chickens of each groups were slaughtered and necropted to evaluate lession score and histopatology of caeca. Oocyst per gram excreta was count on 7th days until 10th days after challenge infection of the others 5 chickens of each groups. The results showed that the lowest score of lession was obtained on M2 and M3 whereas the lowest total oocyst per gram excreta was obtained on M3. Histopathological observation revealed that there was no stadia development of E. tenella in M2 treatment. It was concluded that granule of noni leaves extract at 200 mg/kgbw (M2) was the most effective natural coccidiostat. Key Words: Eimeria tenella, Kenikir Leaves, Noni Leaves, Earthworm Meal, Broiler Chickens